Legal Analysis of Doctors' Responsibilities for the Completeness of Patient Medical Records in the Framework of Fulfilling Patient Rights in Hospitals - Pandega Gama Mahardika (Proceeding of the International Conference on Law and Human Rights, 2024)
Doctors have a legal responsibility to ensure that patient medical records are complete and accurate. A legal analysis of the doctor's responsibility for the completeness of patient medical records in order to fulfill patient rights in hospitals is an important study to ensure that patient rights are fulfilled in accordance with the standards set by applicable laws and regulations. A comprehensive analysis of the doctor's responsibility and the importance of complete medical records is expected to create a better health care system that respects and fulfills patient rights optimally. This study uses a normative legal method. The conclusions of this study are: 1) The doctor's legal responsibility for fulfilling the patient's right to obtain complete Medical Records as a form of the patient's right to information in health services. This right is protected and regulated in a number of legal regulations. Fulfillment of the method of obtaining the contents of Medical Records to patients must also pay attention to and follow the procedures as stipulated in the laws and regulations. 2) The legal consequences of the doctor's legal responsibility if they violate the fulfillment of the patient's right to complete Medical Records, including: 1) criminal sanctions, namely imprisonment for a maximum of 1 (one) year and a maximum fine of Rp. 50,000,000.00 (fifty million rupiah) (Article 79 point b of the Medical Practice Law Law No. 29 of 2004), 2) civil sanctions in the form of compensation by the Hospital or the doctor to the patient (Article 1365 of the Civil Code) and 3) administrative sanctions in the form of written warnings and/or recommendations for revocation or revocation of accreditation status. (Minister of Health Regulation 24 of 2022 concerning Medical Records).